Do sustainable consumers prefer socially responsible investments? A study among the users of robo advisors - Brunen, Ann-Christine; Laubach, Oliver (Journal of Banking & Finance, 2022)
Do people behave consistently when it comes to sustainability? With few exceptions, most previous studies of sustainable investment behavior rely on survey responses. Numerous studies have noted, however, that peoples’ talk is often cheap when it comes to sustainable choices. We use a financially incentivized choice to study the non-investment-related sustainable behavior of the clients of three German robo advisors and relate it to their investment decisions. We find that sustainable consumption translates into a higher likelihood of choosing a portfolio following a sustainable investment strategy among the clients of a digital wealth manager that offers both conventional and sustainable investments. Sustainable consumption also translates into a particularly strong interest in the launch of sustainable investment strategies among the clients of a conventional robo advisor. The provision of sustainable investment strategies can, next to performance and costs, be a selling point for a digital wealth manager. However, our results show that self-reported sustainable consumer behavior that is not backed up by the pertinent actions is not significantly related to sustainable investment choices. Our results lend further support to the notion that studying sustainability in terms of actual choices is crucial. We provide guidance to practitioners in the financial industry on identifying investors with a potential interest in sustainable investments.